Critical Thinking for Cvic Life in Elementary Education: Combining Storytelling and Thinking Tools - Mena Araya, Aarón Elí (2020)
Teaching critical thinking involves developing specific thinking skills and nurturing attitudes that are necessary for adequate use these of these skills in everyday life situations. The required skills and attitudes required by students to approach problems that affect their own communities can be taught by designing and executing learning activities where students use storytelling, for example. This study focuses on designing and executing two learning units for critical thinking instruction on citizenship education in a Costa Rican elementary school.  These units combine the use of story-based materials, such as animated films, digital comic strips, and thinking tools. Additionally, an assessment method is proposed which is  based on analysis of the comic strips created by the students. This method analyzes the logical structure behind comic strips to help determine to what extent critical thinking skills are applied with a focus on specific thinking skills such as inference and analysis. The results of the assessment suggest that when students participate in learning units, such as the use of story-based media and thinking tools, they can express a higher level of critical thinking skill application in the stories they create.